0194 Sleep Quantity And Quality, Pvt-b Performance, And Subjective Sleepiness, Fatigue, And Stress In Commercial Motor Vehicle (cmv) Drivers: On-duty Days Vs. Restart (off-duty) Days. (12th April 2019) - Dinges, David F; Maislin, Greg; Hanowski, Richard J; Mollicone, Daniel; Hickman, Jeffrey S; Maislin, David; Kan, Kevin; Hammond, Rebecca; Soccolich, Susan A; Moeller, Devon; Trantalange, Michael; Cordoza, Makayla; et al.
Abstract: Introduction: An observational study of CMV drivers was undertaken to assess the operational, safety, health, and fatigue impacts of the restart provisions in Sections 395.3(c) and 395.3(d) of Title 49, Code of Federal Regulations. Methods: N=235 drivers (224 males, 20-69y) participated in an observational study for up to 5 months duration. All drivers held a valid CMV driver's license, worked >60 hours/week, completed drives during the day and night, and made use of the restart provisions. They were recruited to reflect diverse types of vehicles and operational distances. They reported either driving mostly during the day (10.2%), mostly during the night (14.9%), or a combination of day and night (74.9%). They were monitored via electronic devices to track driving (including safety critical events) and work hours. Smartphone apps were used to track their behavioral alertness on the Brief Psychomotor Vigilance Test (PVT-B), and their ratings of fatigue, sleepiness, stress, and sleep quality. Statistical comparisons were performed using linear and non-linear mixed-effects modeling. Results: A total of 26, 964 days of data were acquired, including >79, 000 PVT-B tests. During on-duty days, drivers slept an average of 6.6h/day, compared to 8.7h/day during restart (off-duty) days (p<0.0001). During restart periods drivers rated their sleepiness higher (p<0.0001), their sleep quality higher (p<0.0001), and their stress lower (p<0.0001), compared to on-duty days. Drivers' fatigue ratings were higher, and sleep quality ratings were lower, during 1-night vs. 2-night restarts. They had more PVT-B lapses during restart periods than during on-duty periods (p<0.0001), and more lapses when restarts occurred after 168 hours than prior to 168 hours (p<0.0087). Conclusion: Although there were no safety critical events in the study, there was evidence that CMV drivers were in need of more sleep when they undertook a restart as they slept an average of 2h longer during restarts than when they were working. Support (If Any): DTMC75-14-D-00011, Task Order #9